A new lophopid genus as another piece in the biogeographical history puzzle of the family in the Sunda Shelf (Hemiptera: Fulgoromorpha: Lophopidae) - Soulier-Perkins, Adeline; Stroiński, Adam (Zootaxa, 2015)
A new Lophopidae genus Binaluana gen. nov. and species B. emarginata sp. nov. from Palawan are described. Characters are given in order to distinguish this new genus from Bisma and Zeleja that share general figure with it. The morphological characters are coded for the genus and a new phylogenetic analysis using parsimony is performed. The Lophopidae remain monophyletic and Binaluana is placed as sister group of the genus Bisma. (Zeleja (Binaluana+Bisma)) is monophyletic and emerges at the base of the Zeleja+ group. The place of Binaluana within the Lophopidae is discussed along with its historical biogeographic origin.